Construction of Successive Stereogenic Centers of ent-Kauranoid through an Oxidative Dearomatization/1,2-Shift Cascade - Imamura, Yuki; Mizutani, Hikaru; Nakada, Masahisa (Synlett, 2022)
The construction of the successive stereogenic centers, including an all-carbon quaternary stereogenic center, of ent-kauranoid through an oxidative dearomatization/1,2-shift cascade is described. The developed cascade reaction of a substrate bearing a trans-2-(p-methoxyphenyl)vinyl group as the migrating group afforded the desired product in 83% yield. The 1,2-shift in the cascade is strongly affected by a stereoelectronic effect. The X-ray crystal structure of a compound bearing four successive stereogenic centers in the fused-ring moiety of ent-kauranoid diterpene, which was prepared by the oxidative dearomatization/1,2-shift cascade and subsequent stereoselective transformations, is also reported.
Keywords: kauranoid; diterpenes; dearomatization; 1,2-shift reaction; quaternary carbon